Study of the Freeze–Thaw Weathering’s Influence on Thermal Properties of Stone Artifacts - Jia’nan Zhang; Xue Yang; Beichen Chen; Xiangyu Wang; Gangbo Hu; Ning Tao; Jiangang Sun (Atmosphere, 2023)
A study of the weathering process of three types of stones, sandstone, marble, and granite, which are commonly found in artifacts worldwide, is presented. Freeze–thaw cycles are used to accelerate changes in the stone’s physical properties, such as the surface morphology, mass, and porosity. Pulsed infrared thermography, as an in situ non-destructive testing method, is adopted to measure the stone’s thermal properties, such as the diffusivity, effusivity, and conductivity. These thermal parameters influence the natural weathering process, and in turn can change with the decay of the stone materials. Preliminary experimental results show that all three types of stone experience a process of mass loss and porosity increase after the freeze–thaw cycles, and their thermal properties change differently depending on their types. Since the thermal effusivity can be obtained non-destructively by reflectance thermography, we propose for the first time the use of thermal effusivity to characterize the influence of the weathering process and as an indicator of the aging degree of stone artifacts.